High Intensity Interval- Vs Resistance or Combined- Training for Improving Cardiometabolic Health in Overweight Adults (Cardiometabolic Hiit-Rt Study): Study Protocol for a Randomised Controlled Trial - Garcia-Hermoso, A (BioMed Central Ltd., 2016)
Background: Although evidence shows the positive health effects of physical activity, most of the adult population in Colombia are sedentary. It is, therefore, important to implement strategies that generate changes in lifestyle behaviours. This protocol describes a study in which we will compare the effects of 12 weeks of high-intensity interval training (HIIT), resistance training (RT) or combined training (HIIT + RT) on the improvement of body composition, endothelial function, blood pressure, blood lipids, and cardiorespiratory fitness in a cohort of sedentary, overweight adults (aged 30-50 years). Methods/design: Sixty sedentary, overweight adults attending primary care in Bogotá, Colombia will be included in a factorial randomised controlled trial. Participants will be randomly assigned to the following intervention groups: (1) non-exercise group: usual care with dietary support, (2) HIIT group: 4 × 4-min intervals at 85-95 % maximum heart rate (HRmax) (with the target zone maintained for at least 2 minutes), interspersed with a 4-min recovery period, at 65 % HRmax, (3) RT group: completing a resistance circuit (including upper and lower muscle groups) as many times as needed according to subject s weight until an expenditure of 500 kcal at 40-80 % of one-rep max (1RM) has been achieved, and (4) combined group: HIIT + RT. The primary end point for effectiveness is vascular function as measured by flow-mediated vasodilatation 1 week after the end of exercise training. Discussion: The results of this study will provide new information about the possible effect of the programme in improving the cardiometabolic health of overweight adults, making a more efficient use of an adult s resources over time. Trial registration: ClinicalTrials.gov ID: NCT02715063. Registered on 8 March 2016. © 2016 Ramírez-Vélez et al.